Experimental Study of Storing Electrical Energy Generated by an Acoustic Energy Harvester Into a Supercapacitor - Ikhsan Setiawan; Bagas Wahyu Wibowo; Rizki Dwi Prasetya (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Acoustic energy harvester is a device used to convert environmental noise into electrical energy. Many researches on acoustic energy harvesting have been carried out, but most of them have not yet reached the stage of storing the electrical energy produced. This paper presents an experimental study of storing electrical energy generated by an acoustic energy harvester into a supercapacitor. The acoustic energy harvester in this study used a 4-inch woofer loudspeaker as a noise converter into electricity, equipped with a straight cylindrical resonator, a cylindrical housing, and an electric current rectifier unit. The supercapacitor used has a specification of 100F/2.7V. Experiments were carried out by using several variations of the sound frequency with three variations of sound pressure level (SPL) namely 90 dB, 95 dB, and 100 dB, and by measuring the supercapacitor voltage in a charging time of 60 minutes. It was found that the supercapacitor voltage reached 368 mV which was obtained from noise sound with an SPL of 100 dB and a frequency of 54 Hz which gave an initial charging electric current of about 12 mA. In the last five minutes of charging, the increase in supercapacitor voltage was still linear with time at a rate of about 5.2 mV/min. Therefore, the supercapacitor voltage can still significantly increase if the charging continues.